Determination of the required window glazing area based on the targeted illuminance in residences - Uc, Betul; Ozturk, Leyla Dokuzer (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2022)
The European standard EN 17037 for daylight in buildings defines metrics for evaluating the daylight conditions in interior spaces under the headings of daylight provision, assessment for the view out, exposure to sunlight, and protection from glare. There are three levels of recommendation for each specified criterion: minimum, medium, and high. The proposed methods for assessing daylight provision are based on the use of climatic data. So far, no study has been found that examines the glazing area according to the new CEN standard with regard to various parameters such as room shape and size, number of window walls, window position, and direction. The aim of this study is to determine the required glazing area according to the targeted illuminance by considering various options related to the parameters affecting the level of illuminance and to supply data that can be used in residential window design. For this purpose, 1336 residential rooms have been modelled using Diva-for-Rhino software and glazing areas are determined that provide the three levels of illuminance specified in the mentioned standard. The availability of the targeted illuminance levels for half of the daylight hours was calculated using the daylight autonomy method. Climate data for Istanbul were used in the calculations. The effects of obstructions that may be outside the building are excluded from the scope of the study. Some of the factors that determine daylight illuminance have been kept constant. The targeted illuminance level, the shape and size of the room, the number of window walls, window position, sill height, and direction were determined as modifiable factors. Taking into account the dimensions of ordinary living rooms, bedrooms, and children's rooms in residences, 9 square (10 m(2)-50 m(2)) and 14 rectangular (10.8 m(2)-50.4 m(2)) rooms were handled. The ratio between length and width was 1.2, 1.4, 1.6 and 1.8 for rectangular rooms. The conditions of a centred window on one wall and a centred window on each of two adjacent walls were examined. In addition, the cases where the windows are placed off-centred either to the right or left direction were also investigated. The study also includes the comparison of windows with and without a sill. Four cardinal and four ordinal directions were considered. The number of directions considered was sixteen for rectangular rooms with windows on two adjacent walls. Glazing areas were determined that ensure >= 300 lx, >= 500 lx, >= 750 lx illuminance levels in modelled rooms. The illuminance levels >= 500 lx and >= 750 lx could not be achieved in all rooms. Targeted illuminances were attained in 1950 rooms. A comprehensive analysis of the results obtained was carried out. The directions have been ordered from positive to negative, assuming that the direction that provides the target illuminance with the smallest glazing area is the most positive. This order was the same for rooms with a single centred window on one wall but changed for other conditions according to the room geometry. Rooms with equal floor areas but different geometry were compared. It was found that the required glazing area to provide the same illuminance is smaller in rectangular rooms in the case of one window and in square rooms in the case of two windows. The geometric properties of the room and the orientation are decisive for the number, size and position of the windows that provide the desired daylight illuminance. In window design, it is necessary to consider the climatic data of the site where the building is located. This study, which takes into account many variables, presents data that can be used in architectural design. These data can be used in many ways such as positioning the rooms in a building, deciding on the room geometry and size, determining the number and position of windows according to the location of the room in the building and the direction.
Keywords: Glazing area; daylight; room shape; residence; number of windows; Architecture